Local Antimicrobial Therapy with Combined Aminoglycoside and Vancomycin Compared to Aminoglycoside Monotherapy in the Surgical Management of Osteomyelitis and Fracture-Related Infection - Unsworth, A; Young, B; Ferguson, J; Scarborough, M; McNally, M (MDPI, 2024)
We investigated the effect of combination aminoglycoside and vancomycin local antibiotic treatment compared to aminoglycoside alone in the surgical management of bone infection. Data including patient demographics, type of surgery, microbiological characteristics, BACH score, duration of antibiotic treatment and clinical outcomes were collected. Failure of therapy was a composite of recurrence of infection, continued or new antimicrobial therapy, or reoperation with suspected or confirmed infection at one year after index surgery. A total of 266 patients met the inclusion criteria. 252 patients reached the final follow-up and were included in the final analysis. 113 patients had treatment with aminoglycoside alone and 139 patients had combination aminoglycoside and vancomycin. There was no difference in the failure rate between groups; 10/113 (8.8%) in the aminoglycoside alone and 12/139 (8.6%) in the combination group, p = 0.934. Multivariate analysis showed that there was no added benefit of combination therapy (OR 1.54: 95% CI 0.59–4.04, p = 0.38). BACH score and low BMI were associated with increased risk of failure (BACH OR 3.49: 95% CI 1.13–10.76, p = 0.03; Low BMI OR 0.91: 95% CI 0.84–0.99, p = 0.037). The form of the carrier material (pellets or injectable paste) had no effect on failure rate (p = 0.163). The presence of aminoglycoside resistance had no effect on failure rate (OR 0.39: 95% CI 0.05–3.01, p = 0.37). Clinical outcome was not improved by the addition of vancomycin to aminoglycoside alone as local therapy for the management of bone infection.